BioSAXS–an emerging method to accelerate, enrich and de-risk antimicrobial drug development - Rumancev, Christoph; Rosenhahn, Axel; Hilpert, Kai (Frontiers in Pharmacology, 2022)
Antimicrobial resistance is a worldwide threat to modern health care. Low-profit margin and high risk of cross-resistance resulted in a loss of interest in big pharma, contributing to the increasing threat. Strategies to address the problem are starting to emerge. Novel antimicrobial compounds with novel modes of action are especially valued because they have a lower risk of cross-resistance. Up to now determining the mode of action has been very time and resource consuming and will be performed once drug candidates were already progressed in preclinical development. BioSAXS is emerging as a new method to test up to thousands of compounds to classify them into groups based on ultra-structural changes that correlate to their modes of action. First experiments in E. coli (gram-negative) have demonstrated that using conventional and experimental antimicrobials a classification of compounds according to their mode of action was possible. Results were backed up by transmission electron microscopy. Further work showed that also gram-positive bacteria (Staphylococcus aureus) can be used and the effects of novel antimicrobial peptides on both types of bacteria were studied. Preliminary experiments also show that BioSAXS can be used to classify antifungal drugs, demonstrated on Candida albicans. In summary, BioSAXS can accelerate and enrich the discovery of antimicrobial compounds from screening projects with a novel mode of action and hence de-risk the development of urgently needed antimicrobial drugs.